Formulation and Evaluation of Release Kinetics of Diltiazem Hydrochloride from Kollicoat SR 30 D Coated Pellets Prepared by Air Suspension Technique (Bangladesh Journal of Scientific and Industrial Research, 2008)
The purpose of the present study is to investigate the effect of polyvinyl acetate on the release kinetics of diltiazem hydrochloride from coated pellets prepared by solution and suspension layering technique. Kollicoat SR 30 D, an aqueous dispersion of polyvinyl acetate with different weight ratios was chosen to sustain the release of the drug. Drug was loaded with hydroxypropyl methyl cellulose on nonpareil seeds then coated with the Kollicoat SR 30 D. In vitro dissolution studies were carried out using USP dissolution apparatus Type-2. No significant difference was found in drug release from uncoated pellets and the pellets coated with 5% polymer load. With 10% polymer load, the initial release was minimized but from 2nd hour the release was quick-tempered. Better sustaining effect was found from 15- 20% polymer loaded pellets. The mean dissolution time was 2.5h and 4h while the polymer load was 15% and 20% respectively. Also these two cases 80% drug was released at 6h and 9h respectively. The physical parameters of the prepared pellets were also compared in this study. The release of drug from the coated pellets appeared to follow Higuchi's release kinetics.Key words: Diltiazem, Pellets, Kollicoat SR 30 D, Aqueous coating, Physical parameters, Release kinetics.DOI = 10.3329/bjsir.v43i3.1147Bangladesh J. Sci. Ind. Res. 43(3), 321-332, 2008